NUAK1 acts as a novel regulator of PD-L1 via activating GSK-3β/β-catenin pathway in hepatocellular carcinoma - Chao-Yan Yao; Hang-Tian Tao; Jin-Jin He; Feng-Yi Zhu; Cui-Qing Xie; Yu-Na Cheng; Ji-Qin Li; Zhuang-Zhuang Liu; Chun-Yu Hou; Xue-Li Liu; Yong-Li Fan; Dong Fang; et al. (Molecular Medicine)
Abstract Background NUAK1 is associated with metastasis and drug resistance in hepatocellular carcinoma (HCC). However, little is known about the immune functions of NUAK1 in HCC. Therefore, the aim of this study was to elucidate the novel role of NUAK1 in facilitating immune evasion in HCC and to investigate the mechanisms underpinning this process. Method The levels of NUAK1 expression and the infiltration of CD8+ T cells were assessed in tumor tissues from HCC patients and mice xenograft model. HCC cell lines were used to validate the role of NUAK1 in regulating the transcription of PD-L1, the diethylnitrosamine-induced HCC model was established and the expression levels of NUAK1 and PD-L1 proteins in the rat livers were detected. Western blotting, immunofluorescence, real time PCR, and immunohistochemical staining were used to investigate the underlying mechanisms by which NUAK1 regulates PD-L1 expression in hepatocellular carcinoma. Results NUAK1 expression was negatively correlated with CD8+ T cell infiltration in tumor tissues from HCC patients and mice xenograft model. Both gain and loss of functions have identified NUAK1 promoted PD-L1 expression at transcriptional level in HCC cells. The increased expression of NUAK1 and PD-L1 proteins were observed in the rat livers of diethylnitrosamine-induced HCC model. Moreover, overexpression of NUAK1 promotes GSK3β Ser9 phosphorylation, β-catenin expression and nuclear accumulation in HCC cells. By contrast, knockdown of NUAK1 has opposite effects. Inhibition of GSK3β activity significantly promoted β-catenin expression and PD-L1 expression in HCC cells. IHC analyses of tumor tissues from HCC patients suggested that the levels of p-GSK3β and β-catenin were positively correlated with NUAK1 expression. Knockdown of β-catenin also reversed NUAK1-mediated PD-L1 expression in HCC cells. Conclusions This study revealed a novel role for NUAK1, which promotes the transcriptional expression of PD-L1 by activating GSK3β/β-catenin signaling pathway, leading to immune escape of hepatocellular carcinoma. Registry and the registration no. of the study/trial: Not applicable.